Ten-year oncologic outcomes of prostate cancer after robotic-assisted laparoscopic radical prostatectomy: Single center experience - N. Yodkhunnatham (2020)
© Journal of the Medical Association of Thailand. Objective: To evaluate oncologic outcomes after robotic-assisted laparoscopic radical prostatectomy (RALRP) compared with and without neurovascular bundle (NVB) sparing, and to study associating factors that affect biochemical recurrence (BCR) and survival outcome. Materials and Methods: All charts of prostate cancer patients who underwent RALRP during 2007 and 2017 were reviewed. Collected data included demographic information, initial prostate-specific antigen (PSA), operative technique, pathology report, perioperative data, complications, BCR rate, time to recurrence, and overall survival rate. All variables were compared among the non-NVB sparing, unilateral NVB sparing, and bilateral NVB sparing groups. Results: A total of 1,048 patients were included in this study. Pathological staging was pT1 in 2.3%, pT2 in 57.1%, and pT3 in 40.6% of patients. The median follow-up time was 5 years. The BCR rates were 17.3%, 20.0%, and 21.4% in the non-NVB sparing, unilateral NVB sparing, and bilateral NVB sparing groups, respectively (p = 0.339). Unilateral or bilateral NVB sparing had no effect on mean time to BCR (8.83 vs. 8.89 years; p = 0.544). There was no significant difference in 10-year overall survival among the non-sparing, unilateral sparing, and bilateral sparing groups (98.6%, 98.7%, and 99.4%, respectively; p = 0.562). Multivariate analysis confirmed that NVB sparing did not affect the BCR rate (hazard ratio: 1.108, 95% confidence interval: 0.827 to 1.942; p = 0.549). Conclusion: The results of the present study revealed that NVB sparing in RALRP had no significant impact on BCR rate or survival outcome compared to the non-NVB sparing group.